A Big HIIT: A Fracture Dislocation of the Hip in a Young Man Participating in Extreme Conditioning Exercise: A Case Report. Issue 3 (28th July 2020) - Vukanic, D.; Murphy, D.; Juhdi, A.; Leonard, M.
Abstract : Case: Hip dislocations with associated acetabular fracture are rare events usually associated with high-energy trauma. We describe an unusual case of low-energy acetabular fracture dislocation sustained by a 30-year-old athletic male athlete during a high-intensity training program. Conclusion: Correct execution of training programs is important. Healthcare professionals as well as participants and instructors of extreme conditioning programs should be aware of this serious complication. Avoidance of this injury may be possible with increased interval recovery and improved technique.